58.4k views
4 votes
X and Y intercept of y+3=2(x+3)

1 Answer

4 votes

\begin{gathered} \text{Given} \\ y+3=2(x+3) \end{gathered}

Solving for x-intercept

Substitute y = 0 to solve for the x-intercept.


\begin{gathered} y+3=2(x+3) \\ 0+3=2(x+3) \\ 3=2x+6 \\ 3-6=2x \\ -3=2x \\ 2x=-3 \\ (2x)/(2)=(-3)/(2) \\ x=-(3)/(2) \\ \\ \text{Therefore, the }x\text{-intercept is at }(-(3)/(2),0). \end{gathered}

Solving for y-intercept

Substitute x = 0 to solve for y-intercept


\begin{gathered} y+3=2(x+3) \\ y+3=2(0+3) \\ y+3=2(3) \\ y+3=6 \\ y=6-3 \\ y=3 \\ \\ \text{Therefore, the }y\text{-intercept is at }(0,3). \end{gathered}

User Joost
by
5.6k points